Tailoring compressive properties of sintered porous NiTi Alloy for biomedical implant through pore forming agent - Abd Kadir, Nur Amanina; Mohd Zaki, Hafizah Hanim; Abd Samad, Ikhmal Hazrith; Mohd Daud, Farah Diana; Sarifuddin, Norshahida; Abdullah, Jamaluddin (Universiti Putra Malaysia Press, 2023)
Artificial biomaterials should ideally resemble human bones in terms of their structure and properties. The majority of human bones are made of cancellous bone (with 30 to 90% porosity) and cortical bone (with 5% to 30%). Common materials like porous titanium alloy (Ti-6Al-V4) and stainless steel (316L) have been used for implants, however, they don’t match bone elasticity, leading to stress shielding and bone resorption issues. Hence, to mitigate this problem, it is imperative that implant materials closely emulate both low stiffness and high strength characteristics. Porous NiTi alloy was selected primarily for its lower elastic modulus and high strength, which closely aligns with that of human bones. Thus, this study explores the effect of pore forming agent’s concentration on porosity and correlates with compressive behavior of sintered porous NiTi.